The Effect of Using Rehabilitative Exercises to Increase the Flexibility of Wrist Joint for Junior Boxing Players - Dr. Safaa Abdul-wahab Dr. Dunia Abdul-munim (الرياضة المعاصرة, 2019)
The application of rehabilitation exercises to accelerate the healing and get rid of pain because it provides the infected tissues with suitable means to return to its normal condition, and the speed of blood arrival to the injured place, which helps to feed the infected tissues and raise the temperature of the surrounding tissues to get rid of dead and damaged tissues and damaged and calcification by injury, which helps to increase the flexibility of muscles and joints and to increase high nutrient access processes to build damaged tissue and return to normal movement as soon as possible.